The Effect of Teamwork, Work Stress, and Motivation on the Performance of Staff of the Indonesian Armed Forces Finance Center for the Papua Region II - Widodo, Sri; Hattu, Sendy (Dinasti Publisher, 2025)
This study aims to analyze the influence of teamwork, work stress, and motivation on the performance of TNI Finance Center staff for the Papua II Region. This study uses a quantitative approach with a survey method through data collection using questionnaires. The variables studied include teamwork, work stress, motivation, and performance as dependent variables. The results showed that teamwork had a positive and significant influence on performance, while work stress had a negative influence on personnel performance. Motivation was found to have a significant positive influence on performance, reinforcing the role of motivation as an important factor in increasing productivity. These findings make a theoretical contribution to human resource management in the military environment and provide practical implications in teamwork management strategies, work stress control, and motivation enhancement to support personnel performance optimization.